Diffuse infiltrative lymphocytosis syndrome presenting as renal failure in South African HIV-positive individuals: a single-centre case series - McMullen, Kate; Borkum, Megan; Botha, Francois CJ; Duffield, Maureen; Wearne, Nicola (African Journal of Nephrology, 2018)
Diffuse infiltrative lymphocytosis syndrome (DILS) in human immunodeficiency virus (HIV) infection presented most commonly with parotidomegaly and sicca symptoms in the pre-antiretroviral era. However, numerous clinical manifestations are possible due to the multi-organ nature of the CD8+ lymphocytic infiltration. Renal involvement is infrequently described, but common characteristics of a renal syndrome associated with DILS have been identified. This case series describes four South African HIV-positive patients with DILS, in whom renal failure was the sole clinical manifestation. As DILS responds well to antiretroviral and corticosteroid therapy, this series highlights the importance of considering this syndrome as a cause of renal failure in an HIV-positive patient.